PRESSURE INJURY INCIDENCE AND PREVENTIVE MEASURES IN CRITICAL PATIENTS. - Ledo Ferreira, Dalila; Floriano de Souza, Ana Beatriz; Rodrigues, Renne; Willamowius Vituri, Dagmar; Andrade Pereira Meier, Denise (Ciencia, Cuidado e Saude)
Considering that the critical patient is more susceptible to the development of pressure lesions, this study aims to analyze the incidence of pressure lesion in critical patients, and to identify the preventive measures instituted. A cross-sectional study was carried out based on the analysis of 198 medical records of patients admitted in the two intensive care units of a university hospital in southern Brazil between July and December 2015. Data were collected from April to May 2016, using an instrument drawn up by the authors. Subsequently, the data were double-digitized in Epi Info® and analyzed by the Statistical Package for the Social Sciences® program. There is a prevalence of male patients (60.1%), white race (73.2%), mean age 57.5 years-old and the incidence of pressure injury was 39.4%. The most recorded preventive measures (97.9%) were: skin inspection, change of decubitus in every two hours, bedside elevation up to 30º, and use of cushions. There was no association between preventive measures and development of pressure injury. The study showed a high incidence of pressure injury and identified measures for prevention, allowing a reflection on the actions prescribed by the nurse to reduce such events, to promote the health of patients and to improve the quality of nursing care.